2012
DOI: 10.1371/journal.pntd.0001939
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Tetraspanin from the Human Liver Fluke, Opisthorchis viverrini

Abstract: BackgroundThe human liver fluke, Opisthorchis viverrini, is designated as a group 1 carcinogen, and is the major risk factor for cholangiocarcinoma in endemic countries throughout Southeast Asia. Proteins in the excretory-secretory products and tegumental surface membranes of the fluke have been proposed to play pivotal roles in parasite survival in the host, and subsequent pathogenesis. These macromolecules are therefore valid targets for the development of vaccines and new drugs to control the infection. Tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 58 publications
(80 reference statements)
1
48
0
Order By: Relevance
“…In Opisthorchis viverrini the highest expression of Ov-tsp-2 and Ov-tsp-3 was observed in the eggs [42]. In contrast, Piratae et al [27] found highly expressed Ov-tsp-1 in the metacercariae of this species.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In Opisthorchis viverrini the highest expression of Ov-tsp-2 and Ov-tsp-3 was observed in the eggs [42]. In contrast, Piratae et al [27] found highly expressed Ov-tsp-1 in the metacercariae of this species.…”
Section: Discussionmentioning
confidence: 81%
“…No other data are available on the effects of TSP1 suppression in the strobilated forms of E. granulosus. In two studies on adult worms of O. viverrini, treatment by specific dsRNAs, resulted in expression suppression of Ov-tsp-1, Ov-tsp2 and Ov-tsp-3 [27,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ov-grn-1 cDNA was amplified using specific primers as follows: forward primer, Ov -GRN-EXF: 5'-GGGATCGGTTAGTCTAATCTCC-3', and reverse primer, Ov -GRN EXR: 5'-GATCATGGGGGTTCACTGTC) (spanning Ov - grn-1 coding DNA position 6-365) amplifying a 359 bp product which is larger than the dsRNA used for electroporation and therefore cannot be amplified from exogenous dsRNA. The endogenous actin gene (GenBank AY005475) was used as a housekeeping control (Piratae et al, 2012). Real time PCR was carried out using an ABI7500 thermal cycler and the SYBR Green assay.…”
Section: Methodsmentioning
confidence: 99%
“…In Thailand, O. viverrini has attracted intense scientific interest due to the connection of opisthorchiasis and cholangiocarcinoma, a bile duct cancer with a uniquely high prevalence rate in this country (Sripa et al, 2007). Among others, released antigens, tegumental surface antigens and egg antigens of the parasite have been analyzed for their application as diagnostic markers, targets for intervention or their role in tumorigenesis (Ruangsittichai et al, 2006;Pinlaor et al, 2009;Smout et al, 2009;Eursitthichai et al, 2010;Piratae et al, 2012;Sripa et al, 2012) and yet, as this research will demonstrate, antigens of the parasite sperm could also be involved in the host-parasite interaction and might warrant further attention.…”
Section: Introductionmentioning
confidence: 99%